Can Social Networks Substitute for Reputation Systems? Evidence from a Large Scale Field Experiment - Holtz, David; Dow, Alex; Aral, Sinan (AAAI Conference on Web and Social Media, 2026)
Reputation systems are considered by many to be foundational to online peer-to-peer marketplaces. Both economic theory and previous empirical work suggest that centralized reputation should increase trust, increase trustworthiness, and foster marketplace growth. However, prior work also suggests that embedding peer-to-peer commerce in social settings can create trust and obviate the need for centralized reputation. Thus, it is unclear whether we should expect centralized reputation to matter in a setting where social network features are also generating trust. In this paper, we present results from what we believe is the first ever field experiment to randomize the introduction of a reputation system into a massive online marketplace. The setting for our study is an online peer-to-peer marketplace embedded inside of a large social network. We find that on average, the introduction of ratings did not have an effect on the amount of marketplace activity, the behavior of marketplace users, or the structure of the marketplace in the six months following its introduction. Our results suggest that centralized reputation may be unnecessary when online marketplaces are embedded in social networks. Given the number of previously documented biases that can arise in centralized reputation systems, the use of social network data may provide an attractive alternative for online marketplace designers.